New York Heart Association Functional Class correlated with Depression: Study in Saiful Anwar Hospital - Yusuf Arifin; Mohammad Saifur Rohman; Cholid Tri Tjahjono; Djanggan Sargowo; Anna Fuji Rahimah (Heart Science Journal, 2021)
Background: Heart Failure prevalence was raising as one of the most Objective: to find the correlation of New York Heart Association Functional Class in heart failure patient with DepressionMethod: This cross-sectional study recruited 342 patients diagnosed with HF with previously for more than 3 months, at dr. Saiful Anwar General Hospital during December 2016 to March 2021. Each patient was interviewed for their demography data, and their clinical data, and assessed for their depression with Montgomery-Asberg Depression Rating Scale for Indonesian version. We used Spearman coefficients (rs) to evaluate the correlations between variables.Results: Baseline characteristic among depression and non-depression group demonstrated no significant difference (p>0.05), but for marital status. Populations was predominantly male, with ACE-i/ARB and Beta-blockers treatment. Non predominant treatment was MRAs, Diuretics, Digoxin. Baseline age was 22 years old until 87 years old. Baseline LVEF was 50.4±12.9%. (p >0.05). There were significant correlations between NYHA Class and marital status (p < 0.05), while the other baseline was not significantly different. We performed log regression for the confounding. The result was NYHA Class significantly correlated with and effects the depression.Conclusion: In heart failure patients, NYHA Class was significantly correlated with depression.Keyword: NYHA Class; Heart Failure, Montgomery-Asberg Depression Rating Sclae (MADRS), Depression